Transformation of Emotions in Images Using Poisson Blended Generative Adversarial Networks (Student Abstract) - Dernelakis, Aristidis; Kim, Jungin; Velasquez, Kevin; Stearns, Lee (Proceedings of the AAAI Conference on Artificial Intelligence, 2022)
We propose a novel method for transforming the emotional content in an image to a specified target emotion. Existing techniques such as a single generative adversarial network (GAN) struggle to perform well on unconstrained images, especially when data is limited. Our method addresses this limitation by blending the outputs from two networks to better transform fine details (e.g., faces) while still operating on the broader styles of the full image. We demonstrate our method's potential through a proof-of-concept implementation.